‘Higher Laws’ and ‘Divine Madness’: Transnational and Translocal Configurations of Quixotic In/Sanity in the American Renaissance - Bakratcheva, Albena (Review of International American Studies, 2020)
The New England Transcendentalists deliberately chose a position which by definition did not belong to what was to them the common “prosaic mood” (Thoreau) of their time. Their choice was the result of representatively romantic discontent with their contemporary reality and, at the same time, through the vigorous drive of the Puritan spiritual leadership, it was essentially anachronistic. The sophisticated delight of identifying with such a doubly anomalous nonconformist ideal only intensified the need for counterbalancing the prosaic sanity of the real world with a wished-for poetic insanity, or “madness from the gods” (Emerson). Such “madness by romantic identification” whose “features have been fixed once and for all by Cervantes” (Foucault), naturally caused “Quixotic confusion” between reality and imagination and the substitution of the true with the fabulous. Though peculiarly intensified in the former Puritan context and in the context of ‘Americanness’ in which the nineteenth century New England intellectuals placed it, the problem was far from being merely a local, New England-centered, phenomenon. This paper argues that in their ‘in/sane’ Quixotic quest for perfection, which caused a series of personal failures, the New England Transcendentalists were remarkably faithful saunterers in a blessed place that, to them, was both America and, at the same time, the all-encompassing perennial—translocal and transnational—world, inviting them to establish what Emerson called “an original relation to the universe.”